2012
DOI: 10.1128/jb.01381-12
|View full text |Cite
|
Sign up to set email alerts
|

An Extracelluar Protease, SepM, Generates Functional Competence-Stimulating Peptide in Streptococcus mutans UA159

Abstract: Cell-cell communication in Gram-positive bacteria often depends on the production of extracellular peptides. The cariogenic bacterium Streptococcus mutans employs so-called competence-stimulating peptide (CSP) to stimulate mutacin (bacteriocin) production and competence development through the activation of the ComDE two-component pathway. In S. mutans, CSP is secreted as a 21-residue peptide; however, mass spectrometric analysis of culture supernatant indicates the presence of an 18-residue proteolytically cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
102
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 86 publications
(107 citation statements)
references
References 59 publications
3
102
0
2
Order By: Relevance
“…Plasmid pIB184-Km was used as vector for cloning (47). This plasmid contains P23 promoter from lactococcal phage (pOri23).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pIB184-Km was used as vector for cloning (47). This plasmid contains P23 promoter from lactococcal phage (pOri23).…”
Section: Methodsmentioning
confidence: 99%
“…Inactivation of smbAB and smbT genes in GS-5. A previously described fusion PCR method was used for the construction of ⌬smbAB and ⌬smbT mutant strains (47). In short, 500-bp upstream (up) and downstream (dn) flanking regions of the respective genes were separately PCR amplified using GS-5 genomic DNA as a template (see Table 1 for the primers).…”
Section: Methodsmentioning
confidence: 99%
“…Early reports indicated that CSP-18 is more potent and works at a much lower concentration (10-fold) than CSP-21 (13). We recently identified a membrane-associated protease called SepM, which is responsible for the processing of CSP-21 to generate the active QS peptide CSP-18 (8). Surprisingly, genome analysis suggests that S. mutans clinical isolates secrete various CSP subtypes, although the variation among them is not as diverse as that of the pneumococcus CSP (14)(15)(16).…”
mentioning
confidence: 99%
“…SepM contains at least three domains: a transmembrane domain spanning from residues 10 to 26, a eukaryotic-domain-like PDZ domain spanning residues 131 to 195, and a Lon-like proteolytic domain at the C-terminal end (8). As with the Lon protease, this S16 type protease SepM contains a Ser-Lys dyad (S235 and K280) in its active site, in which serine is the nucleophile.…”
mentioning
confidence: 99%
See 1 more Smart Citation